Meningkatkan Aktivitas dan Hasil Belajar Matematika Menggunakan Kombinasi PBL, TPS dan CRH di Sekolah Dasar - Try Suci Septiana; Ahmad Muhyani Rizalie (Universitas Katolik Widya Karya Malang, 2023)
In this study, problems can be found with low activity and student learning outcomes because students still do not understand learning and do not participate in learning. As for the solution to overcome these problems, researchers used a combination of PBL, TPS and CRH models. With the aim of this research to know the activities of students and teachers and improve student learning outcomes. This study uses a type of Classroom Action Research (CAR) with a qualitative approach, in this study conducted for 4 meetings. The research subjects were fifth grade students who were at Sungai Miai 8 Elementary School Banjarmasin with 18 students. The results of this study showed that there was an increase in teacher activity from meeting I reaching a score of 64 in the